Trade Preference Erosion Potential Economic Impacts - Lippoldt, Douglas C.. (OECD Publishing, 2005)
This paper presents the new findings from the on-going work of the OECD project on trade preference erosion. Following a review of the recent literature, the paper develops two main types of analysis. First, a detailed statistical analysis is undertaken drawing on the trade preferences database developed by the Secretariat and covering the Quad countries and Australia. This includes a presentation of the structure of tariff regimes in these key developed countries and identification of countries and sectors that are most reliant on tariff preferences. The second analytical approach uses the standard model and database of the Global Trade Analysis Project to simulate trade liberalisation scenarios that would entail preference erosion. While highlighting a number of cases of preference reliance, the paper underscores the advantages of multilateral liberalisation. Globally and for a majority of developing regions, liberalisation by preference-granting countries will result in positive welfare gains, notwithstanding the effects of preference erosion. In a comparatively small number of cases, however, the analysis points to a risk of net welfare losses under the scenarios modelled here
Keywords: Trade